2006
DOI: 10.1094/mpmi-19-0655
|View full text |Cite
|
Sign up to set email alerts
|

Mi-1-Mediated Aphid Resistance Involves Salicylic Acid and Mitogen-Activated Protein Kinase Signaling Cascades

Abstract: The tomato Mi-1 gene confers resistance to root-knot nematodes (Meloidogyne spp.), potato aphids (Macrosiphum eluphorbiae), and whiteflies (Bemisia tabaci and B. tabaci biotype B). Resistance to potato aphid is developmentally regulated and is not associated with induction of a hypersensitive response. The NahG transgene that eliminates endogenous salicylic acid (SA) was used to test the role of the SA signaling pathway in the resistance mediated by Mi-1 to potato aphids. Aphids survived longer on NahG tomato … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
199
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(221 citation statements)
references
References 52 publications
14
199
0
4
Order By: Relevance
“…LeMPK1/2/3 had been shown to function in host-specific AvrPto-dependent resistance to the bacterial pathogen P. syringae (28,45) and in Mi-1-mediated resistance to aphids (29). Our reduction-of-function study demonstrates that LeMPK1 and LeMPK2 are required for systemin-mediated resistance to M. sexta larvae.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…LeMPK1/2/3 had been shown to function in host-specific AvrPto-dependent resistance to the bacterial pathogen P. syringae (28,45) and in Mi-1-mediated resistance to aphids (29). Our reduction-of-function study demonstrates that LeMPK1 and LeMPK2 are required for systemin-mediated resistance to M. sexta larvae.…”
Section: Discussionmentioning
confidence: 61%
“…Loss-of-function studies had shown they are required for defense against P. syringae and Mi-1-mediated resistance to aphids (29). In this study, we used virus-induced gene silencing (VIGS) and showed that these LeMPKs also function upstream of JA and are required for expression of a subset of wound-response genes and resistance to herbivorous insects.…”
mentioning
confidence: 92%
“…SA and JA are well-established plant signaling molecules that mediate defense responses to insects (Walling, 2000;Li et al, 2006;Zarate et al, 2007;Du et al, 2009;Browse, 2009;Zhao et al, 2016). The transcript levels of SA biosynthesis-related genes accumulated more rapidly and were maintained at higher levels in CC and NB transgenic plants than in wild-type plants.…”
Section: The CC and Nb Domains Activate A Defensesignaling Pathwaymentioning
confidence: 99%
“…By applying VIGS in tomato plants it has been shown that Mi-1.2-mediated resistance against nematodes and aphids requires Hsp90, Sgt1, members of the MAP kinase cascade and WRKY transcription factors (Figure 1) [138][139][140][141]. In addition, by utilizing transgenic tomato plants expressing NahG (encodes for an enzyme that metabolizes SA) a role for SA in Mi-1-mediated resistance to potato aphids was identified [141].…”
Section: Signaling Components Acting Downstream Of Tomato Resistance mentioning
confidence: 99%
“…In a genetic based screening F2 tomato seedlings, those homozygous for the eds1 mutation (eds1/eds1) and those that were heterozygous (EDS1/eds1), were chosen for a disease assay and were inoculated with Fol race 3. Samples were screened for the disease resistance and it was found that EDS1 is required for I-7 mediated resistance [53].By applying VIGS in tomato plants it has been shown that Mi-1.2-mediated resistance against nematodes and aphids requires Hsp90, Sgt1, members of the MAP kinase cascade and WRKY transcription factors (Figure 1) [138][139][140][141]. In addition, by utilizing transgenic tomato plants expressing NahG (encodes for an enzyme that metabolizes SA) a role for SA in Mi-1-mediated resistance to potato aphids was identified [141].…”
mentioning
confidence: 99%